CONTEMPORARY KEBAYA WITH ‘BERKAIN’ GEN-Z THEME THROUGH FRONT BUSTIER AND WASTRA NUSANTARA - Fasya Laksita Putri, Talisa; indarti, Indarti (Universitas Negeri Yogyakarta, 2026)
The kebaya is a traditional Indonesian garment rich in cultural value, but it is often considered irrelevant to younger generations, especially Gen-Z. This study aims to explore the process and results of contemporary kebaya innovation that bridges tradition and modernity through a combination of front bustiers and Wastra Nusantara fabrics, such as batik and songket, with Gen-Z's ‘berkain’ trend. The design method refers to the Double Diamond Model, which includes the following stages: Discover, Define, Develop, and Deliver. The initial stage involves a literature study on the development of kebaya from traditional forms to contemporary interpretations. The second stage is the exploration of ideas used to create a mood board. The third stage is the development of six kebaya illustrations with two themes, namely the charm of pupa with red and pink colors that emphasize elegance and romance, and sunlight with orange and yellow colors that depict joy and positive energy. The final stage is the realization of two selected designs for each theme into actual products through the creation of contemporary kebayas with a combination of front bustiers, obi belts, batik, and songket skirts, as well as decorative details in the form of beads, fringe, and ribbons. The research results show that contemporary kebaya with a modern design approach can still maintain cultural identity through the use of Indonesian textiles, while remaining relevant, aesthetic, and in line with the character of Gen-Z. Keywords: Contemporary kebaya, Berkain, Gen-Z, Front bustier, Wastra Nusantara